PENGARUH PIUTANG MURABAHAH, PEMBIAYAAN MUDHARABAH, MUSYARAKAH DAN PINJAMAN QARDH TERHADAP NET OPERATING MARGIN (NOM) SERTA IMPLIKASINYA TERHADAP NON PERFORMING FINANCING (NPF) BANK UMUM SYARIAH PERIODE 2014-2018 - Munandar, Aris; Romli, Harsi; Zamzam, Fakhry (Jurnal Ecoment Global, 2021)
This research aims to see the influence of Murabahah receivables, Mudharabah Financing, Musyarakah financing, and Qardh loans against Net Operating Margin (NOM) as well as the implications against Non-Performing Financing (NPF). The research object is the Sharia General Bank in Indonesia from 2014-2018. The sampling method used in this research is purposive sampling with selected samples as many as 10 sharia banks out of 14 sharia public banks. Data were analyzed by using a panel regression analysis model, and it was processed in Eviews 10. The results showed that the Murabahah receivables have a significant and negative effect on Net Operating Margin (NOM), with a coefficient value of-1.08 E-11 and a prob. amounting to 0.0470. Mudharabah financing has a significant and positive effect on Net Operating Margin (NOM), with a coefficient value of 4.98 E-11 and a prob. of 0.0137. Musyarakah financing has a positive effect on Net Operating Margin (NOM), with a coefficient value of 2.97 E-12 and prob. by 0.1579. Qardh loans have a negative effect and not significant to Net Operating Margin (NOM), with a coefficient value of-2.88 E-09 and prob. of 0.4773. Besides, receivables Murabahah, financing Mudharabah, Musyarakah, and Qardh loans have a significant effect on Net Operating Margin (NOM) simultaneously. Net Operating Margin (NOM) significant negative effect on Non-Performing Financing (NPF), with a coefficient value of-0.165482 and prob. of 0.0126Key words: Murabahah, Mudharabah, Musyarakah, Qardh, NOM, NPF